Mobile-Based Geographic Information System of School Mapping in Tanjung Batu District - Sasrimita, Sasrimita (Jurnal Manajemen Informatika Medicom (JMI), 2025)
The implementation of national education must ensure equity and improve the quality of education in the midst of global changes, so education must be carried out as well as possible by the government and the community in an integrated manner both in construction and in determining the location of schools to obtain complete information about schools, both elementary and high school levels in Tanjung Batu sub-district. This study aims to create an application for a Geographic Information System for Mapping Schools in Tanjung Batu District based on Mobile with the method used using the waterfall model. The design editor uses Eclipse software and uses Google Maps to display a map of the distribution of schools in Tanjung Batu District in the form of an Android smartphone application. Based on this research, it can be seen the locations of schools in the Tanjung Batu District which allows users to search and find out pertinent information at each school, starting from the elementary, junior high, MTs, MA, SMA to SMK levels in Tanjung Batu sub-district.